A UPLC/ESI–MS method for identifying wool, cashmere and yak fibres. Issue 9 (June 2014) - Vineis, Claudia; Tonetti, Cinzia; Paolella, Sara; Pozzo, PierDavide; Sforza, Stefano
A new objective method has been developed for the identification of animal hair fibres, in particular wool, cashmere and yak. Enzymatic digestion of keratin extracted from these fibres and peptide analysis by ultra-performance liquid chromatography/electrospray–mass spectrometry (UPLC/ESI–MS) allows not only qualitative determination of the presence of fibres derived from these species but also a quantitative assessment of the relative percentages present in blends. Such an analysis will provide reliable objective data about the authenticity of commercial products. The effectiveness of the UPLC/ESI–MS method was assessed by analysing known samples of these fibres and confirmed using unknown wool/cashmere/yak blends, and the results were compared with those obtained by SEM method IWTO 58–00.